2008
DOI: 10.1080/08820130701410223
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-derived Mesenchymal Stem Cells Decrease Acute Graft-versus-Host Disease after Allogeneic Hematopoietic Stem Cells Transplantation

Abstract: Graft-versus-host disease is a major complication of allogeneic hematopoietic stem cells transplantation, leading to serious morbidity and mortality. Mesenchymal stem cells(MSC)from bone marrow cause immunoregulation in vitro and in vivo. They also have the potential to protect from lethal GVHD after both autologous and allogeneic Hematopoietic Stem Cells Transplantation (HSCT). In this study, we investigated the mechanisms responsible for GVHD in the allo-HSCT co-transplantation with MSC condition. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…After 10 6 cells were plated in Ø100 mm culture dish, cells were incubated with DMEM/F-12 media containing 20% FBS, 200 IU/ml penicillin and 250 μg/ml streptomycin for 48 h. The HSCs were purified from nonadherent cells after removing the RBCs by using the distilled water and adherent cells were collected as MSCs. The purified BMDMSC was identified by CD 44 staining (Tian et al, 2008) and BMDHSC was identified by CD45 staining. The fourth to sixth passages were used for individual chemotactic experiments.…”
Section: Migration Assaymentioning
confidence: 99%
“…After 10 6 cells were plated in Ø100 mm culture dish, cells were incubated with DMEM/F-12 media containing 20% FBS, 200 IU/ml penicillin and 250 μg/ml streptomycin for 48 h. The HSCs were purified from nonadherent cells after removing the RBCs by using the distilled water and adherent cells were collected as MSCs. The purified BMDMSC was identified by CD 44 staining (Tian et al, 2008) and BMDHSC was identified by CD45 staining. The fourth to sixth passages were used for individual chemotactic experiments.…”
Section: Migration Assaymentioning
confidence: 99%
“…At present, three major fi elds can be identi fi ed, in which MSC can and will be used for therapeutic purposes: (I) tissue repair Mazhari and Hare 2007 ;Müller et al 2008b ) ; (II) therapy of chronic graft vs. host disease (GvHD) (Aksu et al 2008 ;Le Blanc et al 2008 ;Tian et al 2008 ) , and (III) enhancement of hematopoietic stem cell engraftment in an allogeneic transplant setting Müller et al 2008a ) . The underlying key mechanism in all the three fi elds is not completely understood, but probably a result of MSC-induced immunosuppression.…”
Section: Conclusion and Future Development In Researchmentioning
confidence: 99%
“…It is popular attended as appropriate seed cells [5,6]. There were increasing evidences that transplanted BMSCs significantly promote nervous functional recovery after Central Nervous System (CNS) injured in the animal models [7][8][9]. The BMSCs treatment for neural disease would be of great benefit, but the mechanism is still unclear [6,10,11].…”
Section: Editorialmentioning
confidence: 99%